Simulation-based E-communication as a Reflective Learning Tool for Nursing Students - Hæsum, Lisa Korsbakke Emtekær; Klit, Mona Østergaard (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
Simulation-based training in e-communication offers nursing students a valuable opportunity to develop critical competencies for contemporary healthcare practice. At the University College of Northern Denmark (UCN), this training incorporates realistic scenarios such as telemedicine consultations and virtual interprofessional collaboration, enabling students to engage in experiential, reflective learning. Grounded in a pedagogical approach emphasizing iterative cycles of action, reflection, and feedback, the training supports the development of effective digital communication strategies. Structured debriefing sessions foster self-assessment, empathy, and professional accountability, deepening students' understanding of their roles in virtual care settings. This qualitative study explores students’ experiences of e-communication simulation through open-ended survey responses, analysed using Braun and Clarke’s thematic analysis. Five overarching themes emerged: (1) navigating digital communication and relationship-building; (2) simulation as a catalyst for experiential learning; (3) technological uncertainty as authentic disturbance; (4) the role of preparation and psychological safety; and (5) role exploration and interprofessional perspective-taking. These themes reflect how the simulations fostered adaptive communication, critical thinking, and collaboration. Moreover, the design effectively operationalized pedagogical principles of learning through challenge and exploration, encouraging students to navigate uncertainty and construct knowledge through interaction. Findings underscore the value of simulation-based e-communication training in preparing nursing students for the complexities of digital healthcare. By promoting reflection, adaptability, and interprofessional awareness, such training offers a robust framework for cultivating essential competencies in virtual care environments.